Downsized Sheath–Core Conducting Fibers for Weavable Superelastic Wires, Biosensors, Supercapacitors, and Strain Sensors. Issue 25 (2nd May 2016) - Wang, Hongyan; Liu, Zunfeng; Ding, Jianning; Lepró, Xavier; Fang, Shaoli; Jiang, Nan; Yuan, Ninyi; Wang, Run; Yin, Qu; Lv, Wei; Liu, Zhongsheng; Zhang, Mei; et al.
Abstract : Hair‐like‐diameter superelastic conducting fibers, comprising a buckled carbon nanotube sheath on a rubber core, are fabricated, characterized, and deployed as weavable wires, biosensors, supercapacitors, and strain sensors. These downsized sheath–core fibers provide the demonstrated basis for glucose sensors, supercapacitors, and electrical interconnects whose performance is undegraded by giant strain, as well as ultrafast strain sensors that exploit strain‐dependent capacitance changes.